On the angular resolving powers of cross-loop/monopole antenna arrays based on the music algorithm - Shi, Xin-Zhi; Wen, Bi-Yang; Wang, Gaofeng; Wang, Bing-Zhong (Microwave and optical technology letters, 2003)
To increase HF‐GWR portability, it is very desirable to use smaller antennas yet achieve higher angular resolving power. Based on the MUSIC algorithm, the angular resolving powers of various combined cross‐loop/monopole and monopole antenna arrays are studied with variations of target angles, signal‐to‐noise ratio, and sampling density. It is found that a combination of two cross‐loop/monopole antennas plus one monopole antenna gives the best performance. © 2003 Wiley Periodicals, Inc. Microwave Opt Technol Lett 39: 171–175, 2003; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.11160